Cascading time-frequency domain filtered-x LMS algorithm for active control of uncorrelated disturbances. (June 2019) - Padhi, Trideba; Chandra, Mahesh
Abstract: The presence of uncorrelated disturbances at the error sensor of an active noise control (ANC) system has become very common with increase in the use of industrial machinery such as rotating machines, fans, vehicular motors, etc. The feed-forward ANC system employing filtered-x least mean squares (FXLMS) algorithm to solve this problem has not produced acceptable noise canceling performance. We propose a new cascading time-frequency domain FXLMS algorithm for active control of uncorrelated disturbances in a feed-forward ANC system. In the proposed method, the error signal of the ANC system containing the uncorrelated disturbances is decomposed into various band-limited parts using the discrete wavelet transform (DWT). Dividing the uncorrelated disturbance into various parts enables independent analysis of each part resulting in improved accuracy of error modeling. As a result of this multi-resolution analysis of the error signal, a superior noise canceling performance is achieved. Numerical simulations validate that the proposed algorithm outperforms its counterparts in terms of noise canceling performance and achieves faster adaptive filter convergence as well.